Ediacaran paleoenvironmental changes recorded in the mixed carbonate-siliciclastic Bambui Basin, Brazil - Uhlein, Gabriel J.; Uhlein, Alexandre; Pereira, Egberto; Caxito, Fabricio A.; Okubo, Juliana [UNESP]; Warren, Lucas V. [UNESP]; Sial, Alcides N. (Elsevier B.V., 2019)
Significant Ediacaran paleoenvironmental changes recorded in the mixed carbonate-siliciclastic Bambui Basin, east-central Brazil, outcrop in one of the best-preserved sites, the Januaria paleo-high. From a detailed strati graphic and chemostratigraphic approach (carbon and oxygen isotopes, total organic carbon, total sulfur and selected elements abundances), we identified transgressive-regressive intervals and depositional settings within the Barnhill Group stratigraphy and developed a new model for the origin of the extremely positive Middle Bambui Excursion (MIBE) present in the middle section of the basin. A post-Marinoan cap carbonate interval is recorded in the first similar to 10 m, preserving aragonite pseudomorph fans, barite-rich layers and negative delta C-13 anomaly. A hiatus separates the cap carbonate from the late Ediacaran succession that makes up the remaining Bambui Group. The younger intervals preserve both siliciclastic (middle Serra de Santa Helena Formation) and carbonate (middle/upper Sete Lagoas and Lagoa do Jacare formations) shallow-water depositional settings, requiring tectonic influence or climatic changes in source areas. The MIBE yields delta C-13 values as high as +14 parts per thousand and extends for about 350 m, from the upper Sete Lagoas Formation to the lower Serra da Saudade Formation. We suggest a model of a restricted basin setting that favored local carbon isotopic signals in the delta C-13 record of sedimentary carbonates through preferential weathering of ancient carbonate platforms on the continent and higher burial rate of authigenic carbonate. This scenario caused the global delta C-13 budget to be affected by an offset of, at least, + 4 parts per thousand in sedimentary carbonates deposited on the Sao Francisco craton and along its margin during the terminal Ediacaran. Many previous studies suggested a restricted nature for the middle Bambui Basin, which probably resulted from the central position of the Sao Francisco paleocontinent within the mosaic of collisional blocks during the SW Gondwana amalgamation.
Keywords: West Gondwana; Paleogeography; Depositional settings; Chemostratigraphy; Carbon isotope excursion; Carbon burial